MAKING OF IRON NUGGET FROM CONCENTRATED IRON SAND USING MINI-SIZED ROTARY KILN - Nuryadi Saleh; Siti Rochani; Hasudungan Eric Mamby (Indonesian Mining Journal, 2017)
The availability of energy becomes a major problem in the construction of iron mineral-based smelter to produce ferrous metals in the form of pig iron. Therefore, it is necessary to develop the Krupp-Renn technology that based on coal as a reducing agent to produce pig iron in the form of nuggets. Such a technology employs a rotary kiln that consumes less energy than other furnaces. In this study, reduction process of iron sand concentrates with coal as the reductant was accomplished in a mini-sized rotary kiln (0.6 m diameter and 6 m length). The process of iron nugget making from iron sand concentrate was conducted in two (2) stages, namely oxidation and reduction processes. The former was accomplished at a temperature above 800°C for 2 (two) hours to produce hematite phase. While the later was carried out at 1250-1300°C for 6-8 hours. Both processes produced iron nuggets that contained more than 90% Fe. The highest Fe content reached 96.49% Fe. Such a nugget could meet the requirement for steel making.